Fahrs Disease: A Rare Neurodegenerative Disorder in Children - Rahman, AKMM; Begum, RS; Hossain, MZ; Ali, MR; Rahman, M (Journal of Dhaka Medical College, 2011)
A case of Fahr’s disease in reported in a 2 year 9 month old male child presented with developmental delay and seizure. The CT scan of brain showed multiple symmetric calcifications in the basal ganglia, thalamus, and subcortical white matter of cerebral and cerebellar areas. No underlying cause for the bilateral calcification was found. This rare case of Fahr’s disease in a child, which has never been reported in Bangladeshi literature, has been brought out to highlight this unusual condition. Key words: Fahr’s disease; basal ganglia; calcification. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8589 J Dhaka Med Coll. 2011; 20(1) :86-88